Taxonomic review of Stictophaula (Orthoptera: Phaneropterinae) with the description of one new species from Brunei Darussalam - Tan, Ming Kai; Wahab, Rodzay Bin Haji Abdul (Zootaxa, 2017)
Stictophaula Hebard, 1922 is a genus of katydid from the subfamily Phaneropterinae, and most similar to Arnobia Stål, 1876. A review of the genus Stictophaula reveals 26 species from Southeast Asia. One new species, Stictophaula bruneii sp. nov., is described from Brunei Darussalam. Nomenclature change is also verified: Arnobia ocellata comb. nov. An illustrated key to species is presented.